Perceptions of privacy in interior spaces among selected Filipino female middle-class individuals - Cance, Celeste Marie A.
This qualitative and descriptive study sought to examine the definition of privacy in the home as perceived by selected female Filipino middle-class individuals by investigating their perceptions and preferences towards privacy in terms of space layout, furniture arrangement and structural components in specific areas of their homes. Five females within the age bracket of 25-40 who lives with their family in Makati were chosen by purposive sampling. They were interviewed to gather data for the study. The results and findings revealed that culture, personality and background influence the respondents' concept of privacy and preferences of toward space. The definition of privacy that emerged is that privacy is both a boundary and a connection of the self to others and the environment. Likewise, the findings suggest that though respondents have one definition of privacy, the mechanisms to achieve it vary as shown among the differences of their preferences towards their residential interior spaces.